Impact of endometriosis on risk of further gynaecological surgery and cancer: a national cohort study. (27th September 2017) - Saraswat, L; Ayansina, D; Cooper, KG; Bhattacharya, S; Horne, AW; Bhattacharya, S
Abstract : Objective: To evaluate the long‐term risk of further gynaecological surgery and cancer in women with endometriosis. Design: Cohort study. Setting: Scotland. Participants: 281 937 women with nearly 5 million person years (4 923 628) of follow up from 1981 to 2010. Methods: In this national population‐based study we compared 17 834 women with a new surgical diagnosis of endometriosis with 83 303 women with no evidence of endometriosis at laparoscopy, 162 966 women who underwent laparoscopic sterilisation, and 17 834 age‐matched women from the general population. Cox proportional hazards regression was used to calculate crude and adjusted hazard ratios with 95% confidence intervals. Main outcome measures: Risk of further gynaecological surgery, number and type of repeat surgery and time to repeat surgery from the diagnosis of endometriosis. Cancer outcomes included subsequent risk of all cancer, gynaecological and non–gynaecological cancers. Results: Women with endometriosis had a significantly higher risk of further surgery when compared with women with no evidence of endometriosis at laparoscopy [hazard ratio (HR) 1.69, 95% (confidence interval) CI 1.65–1.73], women who had undergone laparoscopic sterilisation (HR 3.30, 95% CI 3.23–3.37) and age‐matched women from the general population (HR 5.95, 95% CI 5.71–6.20). They also have an increased risk of ovarian cancer when compared with general population counterparts (HR 1.77, 95% CI 1.08–2.89) or those with laparoscopic sterilisation (HR 1.75, 95% CI 1.2–2.45). Conclusion: Women with surgically diagnosed endometriosis face an increased risk of multiple surgery. They have a higher chance of developing ovarian cancer in comparison with the general population and women with laparoscopic sterilisation. Tweetable abstract: Women with endometriosis face an increased risk of recurrent surgery and developing ovarian cancer. Tweetable abstract: Women with endometriosis face an increased risk of recurrent surgery and developing ovarian cancer.